(untitled) (Confluenţe Bibliologice, 2022)
This article is about the impressive album-catalogue , Royal Portraiture. Art and memory», foreword by Narcis Dorin Ion and Mircea Alexandru Hortopan, who confess about extraordinary power of suggestion of artists, but also the image of a royal Romania, in which the monarch had to assume, through image and symbol, the power and good aspirations of the nation Romanian. On this occasion, the Peleș National Museum organized an exhibition, with the generic above, which proposes the portraits of the sovereigns of Romania and their family members.